1998
DOI: 10.1111/j.1460-2466.1998.tb02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Analysis of Sexual Etiquette in Teenage Magazines

Abstract: Expanding on existing research on women's magazines, this essay examines the sexual etiquette developed in advice columns in magazines popular among teenage women. Over a span of 20 years, the advice has changed very little. Serving the rhetorical function of field guides and training manuals, teen magazines limit women's sociality and sexuality within narrowly defined heterosexual norms and practices. The rhetoric of sexual etiquette encourages young women to be sex objects and teachers of interpersonal commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 10 publications
1
65
0
1
Order By: Relevance
“…Relatively little research is available on this topic, and what is available is largely concerned with magazines targeted at young women. A broad range of sexual topics are apparently available in women's magazines such as Cosmopolitan, including topics as diverse as contraception, sexual technique, and sex addiction, though sexual techniques and pleasuring seem to be most common (Bielay & Herold, 1995); topics of magazines targeted at younger women generally focus on establishing and maintaining romantic relationships and sexual decision-making, though sexual health issues and techniques are also present (Carpenter, 1998;Garner, Sterk, & Adams, 1998). Magazines targeted at adolescent girls, such as Seventeen and YM, have been found to contain conflicting messages about sex; they encourage girls to be sexy, emphasize the importance of romantic relationships, instruct young women on how to please young men, and simultaneously emphasize patience and control (Carpenter, 1998;Durham, 1998;Garner et al, 1998).…”
Section: Sexual Messages In Popular Magazinesmentioning
confidence: 98%
See 1 more Smart Citation
“…Relatively little research is available on this topic, and what is available is largely concerned with magazines targeted at young women. A broad range of sexual topics are apparently available in women's magazines such as Cosmopolitan, including topics as diverse as contraception, sexual technique, and sex addiction, though sexual techniques and pleasuring seem to be most common (Bielay & Herold, 1995); topics of magazines targeted at younger women generally focus on establishing and maintaining romantic relationships and sexual decision-making, though sexual health issues and techniques are also present (Carpenter, 1998;Garner, Sterk, & Adams, 1998). Magazines targeted at adolescent girls, such as Seventeen and YM, have been found to contain conflicting messages about sex; they encourage girls to be sexy, emphasize the importance of romantic relationships, instruct young women on how to please young men, and simultaneously emphasize patience and control (Carpenter, 1998;Durham, 1998;Garner et al, 1998).…”
Section: Sexual Messages In Popular Magazinesmentioning
confidence: 98%
“…A broad range of sexual topics are apparently available in women's magazines such as Cosmopolitan, including topics as diverse as contraception, sexual technique, and sex addiction, though sexual techniques and pleasuring seem to be most common (Bielay & Herold, 1995); topics of magazines targeted at younger women generally focus on establishing and maintaining romantic relationships and sexual decision-making, though sexual health issues and techniques are also present (Carpenter, 1998;Garner, Sterk, & Adams, 1998). Magazines targeted at adolescent girls, such as Seventeen and YM, have been found to contain conflicting messages about sex; they encourage girls to be sexy, emphasize the importance of romantic relationships, instruct young women on how to please young men, and simultaneously emphasize patience and control (Carpenter, 1998;Durham, 1998;Garner et al, 1998). Studies of magazines targeted at adult audiences, both male and female, such as Cosmopolitan, Self, GQ, and Playboy, have demonstrated that their contents treat women as sex objects, both through use of objectifying images (Krassas, Blauwkamp, & Wesselink, 2001) and the written content of articles about relationships (Duran & Prusank, 1997).…”
Section: Sexual Messages In Popular Magazinesmentioning
confidence: 98%
“…(Santa Cruz, 1995, pp. 52-53) Popular magazines are dominated by portrayals of women as being primarily interested in beauty, fashion, and heterosexual romantic relationships (Duffy & Gotcher, 1996;Evans, Rutberg, Sather, & Turner, 1991;Ferguson, 1983;Garner et al, 1998;Hermes, 1995;McCracken, 1993;Peirce, 1990Peirce, , 1995Steiner, 1995;Wolf, 1992), including teen magazines, which are essentially focused on promoting heterosexual romance as the central project of a woman's life (Peirce, 1990;Schlenker, Caron, & Halteman, 1998) and establishing men as the dominating force of romantic relationships (Carpenter, 1998;Durham, 1996Durham, , 1998Garner et al, 1998). Duffy and Gotcher find that popularity and romance is emphasized to teens to a degree that creates a ''distorted world view ...where success is determined by meeting the needs and expectations of males '' (1996, p. 45).…”
mentioning
confidence: 99%
“…Lana F. Rakow (2001) argues that "media texts do not present messages about our culture; they are culture'' (42; emphasis added). Popular media act as socializing agents, educating audiences in their place in society (Ferguson, Kreshel, and Tinkham 1990;Garner, Sterk, and Adams 1998). Edward Herman and Noam Chomsky (1988) identify mass media representations as having the power to teach social values and beliefs to its audiences.…”
Section: Literature Reviewmentioning
confidence: 99%